TECHNOLOGICAL DEVICES IN THE CLASSROOM: ANALYSIS OF BENEFITS, CHALLENGES AND EDUCATIONAL PERSPECTIVES - Diego Alexander Ramírez Pérez; Yadira Andrea Acosta Basto; Francia Jasneth Guapacha Peláez (DIALÉCTICA, 2026)
This article presents a comprehensive overview of the use of technological devices—such as computers, mobile phones, personal devices, and tablets—as well as digital platforms, within the classroom. The review process involved analyzing specialized literature in the fields of education and health, making it possible to identify both their contributions and the associated issues. The findings highlight both the benefits and the challenges involved; the integration of these devices into instructional practice has marked a significant step forward in teaching, fostering interest and motivation, providing access to a wide range of digital resources, and encouraging collaborative work, among other advantages. However, their use presents challenges that extend beyond the scope of pedagogical practice itself; various studies have shown that the use of these technological devices and digital platforms can impact the mental well-being of children and young people, leading to issues such as addiction, anxiety, and difficulties with emotional regulation—particularly in cases of excessive use and a lack of regulation. Furthermore, the digital divide has exposed inequalities in access and underscored the urgent need for teacher training to ensure their use is pedagogical, effective, and responsible. In conclusion, technological devices can be powerful allies in the educational process, provided they are supported by educational policies that regulate equitable access and promote students’ holistic development, and are accompanied by trained teachers capable of guiding their balanced use to foster appropriate educational perspectives for the future